‘Where is the large garden that awaits me?’ Critique through spatial practice in a Hungarian ecological community - Farkas, Judit (Socio.hu Társadalomtudományi Szemle, 2016)
Hungarian ecovillage dwellers are mostly ‘moved–out–of–town’, i.e. ex–urban, middle–class intellectuals whose narratives, besides the crisis–narrative and ecological principles, contain an urban–rural dichotomy as well. The ecovillagers’ aim is to operate a settlement causing as little damage as possible to the natural environment as well as to set up an autonomous community where functions necessary for human life (housing, employment, suitable environment for leisure time, social life and trading) can be implemented in one place. The village is considered to be the most ideal form for this. One of the main elements in the ecovillage concept is therefore space and localization. Ecovillages, due to their specific condition, raise many questions in relation to space, place and identity: what motivates the ecovillage dwellers to change location and what critical elements are there. Do they experience real bonding with the new place? Do they belong to that particular land, the settlement, or rather to the ideology? What spatial practices characterize this type of settling down and how does the given ecovillage become a meaningful place and home for individuals? The aim of this study was to look for answers in one particular community. Key words: ecovillage, radical rurality, localization, critique–through–spatial–practice